Enhanced microalgae cultivation using digested kitchen waste sewage treated with struvite precipitation - Chaoyu, Tian; Xiao, Ye; Yingying, Xu; Wei, Hua; Wanqing, Wang; Shuang, Wu; Chen, Paul; Yanling, Cheng (International Journal of Agricultural and Biological Engineering, 2017)
This study demonstrated the feasibility of using struvite for nutrient management in algae cultivation on sewage wastewater. The results showed that struvite precipitation treatment dramatically reduced the ammonia in the digested kitchen waste sewage. The untreated sewage was unable to sustain continuous growth of algae, while the algae growth on the treated sewage was comparable with that on an artificial algae culture medium (BG11). The rapid growth on the treated sewage was accompanied by substantial removal of nutrients. The struvite precipitate recovered from the treated sewage was proven to be an alternative source of nitrogen, phosphorus and magnesium. The struvite precipitate was evidenced that it could substitute culture media in algae growth. This study showed that struvite treatment is viable for nutrient management of algae cultivation on sewage wastewaters which do not have suitable nutrient profiles.Keywords: digested kitchen waste sewage, microalgae, nutrients removal, struvite precipitation treatmentDOI: 10.3965/j.ijabe.20171001.2318Citation: Tian C Y, Ye X, Xu Y Y, Hua W, Wang W Q, Wu S, et al. Enhanced microalgae cultivation using digested kitchen waste sewage treated with struvite precipitation. Int J Agric & Biol Eng, 2017; 10(1): 142–147.